Corporate ESG Ratings and Green Innovation: Evidence from China’s A-Share Manufacturing Firms - Gu, Ziting (International Journal of Social Sciences and Public Administration, 2026)
In the new stage of economic development, environmental, social, and governance (ESG) is an important sustainability-oriented concept for corporate operations. Under the green development agenda, how to embed a firm’s multiple responsibilities-environmental, social, and corporate governance-into its innovation system to drive the transformation from conventional innovation to green innovation has become a key research topic. Using data on China’s A-share listed manufacturing firms from 2009 to 2021, this study empirically examines the effect of ESG ratings on firms’ green innovation output. The results show that higher ESG ratings are associated with greater green innovation output, and the conclusion remains robust across multiple robustness checks. Mechanism analysis further suggests that improved ESG ratings can alleviate financing constraints, thereby promoting green innovation. This study provides policy implications for strengthening ESG practices and integrating sustainability and corporate social responsibility into firms’ innovation systems, ultimately facilitating green transformation and the co-development of firms, society, and the environment.